The Brahmaputra Water dispute: India–China relations and regional security - Sharmistha Hazra; Sitakanta Mishra (Faculty of Social and Political Science, Universitas Airlangga, 2026)
This study examines the regional security dimension of the India-China water dispute over the Brahmaputra in South Asia. It also seeks to understand how China is considered part of South Asia rather than an outsider. Drawing on theories of hydro-politics, realism, liberalism, and regional security complexes, this article investigates whether the water dispute is merely an extension of the border conflict or a manifestation of deeper, structural rivalries. Additionally, it explores the hegemonic tendencies exhibited by both nations as upper riparian states. A qualitative approach has been employed to gather and analyse the data. The findings of this study indicate that the water dispute has disturbed the peace and stability of South Asia. It also finds that China is part of South Asia owing to its geographical location and colonial history. The study concludes that, although the risk of large-scale warfare remains low, effective collaboration is vital for regional stability. This study recommends that India and China should collaborate to resolve their border and water disputes.